IBU DIABETES MELLITUS GESTATIONAL (DMG) DENGAN HIPOGLIKEMIA NEONATORUM - Guntur Budi W; Sriami .; Riska Fauziyah (Poltekkes Kemenkes Surabaya, 2014)
The method used is an analytical survey with cross-sectional approach. Independent variable maternal Gestational Diabetes Mellitus (GDM), while the dependent variable neonatal hypoglycemia. Sampling techniques using non-probability sampling by consecutive sampling. Population as 324, while the 70 samples used maternity and baby. Collecting primary data by sampling pheriperal blood using a gluco test on maternal and infants born to these mothers. Test statistic is Yate’s Corrections. The results illustrate that the maternal 21 DMG almost all barbies are born experiencing neonatal hypoglycemia which 18 (85.71%). Of 49 women giving brith are not DMG almost all barbies born are not experienced neonatal hypoglycemia are 48 (97.96%). Statistical test results Yate’s Correction with a significance level (α) of 0.05 or 95% confidence level to mention that a significant level (ρ) DMG mothers with neonatal hypoglycemia 0.000 smaller than α = 0.05 (0.0000.05), and the results manual calculations using the same formula with Yate’s Correction Continuity Correction on SPSS results, is 47.898. then